Side Effects of Neoadjuvant Chemotherapy for Nasopharyngeal Carcinoma - Genggam Jagad Agami; Yussy Afriani Dewi; Ongka Muhammad Saifuddin (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is a squamous cell carcinoma of the mucosal nasopharynx with a unique geographical distribution which particularly prevalent in the east and southeast Asia. While nasopharyngeal carcinoma is a highly radiosensitive tumor, chemotherapy is added to enhance the effect of treatment. The therapeutic side effect is one of many factors that need to be considered when choosing the treatment method. Therefore, this study is conducted to address the side effect of neoadjuvant chemotherapy. Objective: This study is conducted to address the side effect of neoadjuvant chemotherapy. Methods: This study was a retrospective cohort study with total sampling method of all NPC patients in Hasan Sadikin General Hospital 2015-2019 period. Results: From a total of 247 subjects, NPC occurred in 180 men (72.87%). The most widely used regimen was Cisplatin + 5FU which is used in 187 patients (75.70%). There were several side effects caused by NPC chemotherapy including vomiting, nausea, fatigue, weight loss, dermatitis, stomatitis, hepatotoxicity, ototoxic, diarrhea, leucopenia, neutropenia, thrombocytopenia, and anemia. Conclusion: The most common side effect of cisplatin+5FU were ototoxicity therefore, audiometric examination both before and after administration of chemotherapy. Laboratory examination was needed for the administration of carboplatin+paclitaxel to monitor the side effects of neutropenia.